Vestibular Compensation following Retrosigmoid Vestibular Schwannoma Surgery. (23rd August 2013) - Betka, Jan; Chovanec, Martin; Zverina, Eduard; Profant, Oliver; Cakrt, Ondrej
Abstract : Objectives: Balance problems following vestibular schwannoma (VS) surgery are most apparent in the acute stage and usually improve over time. Persisting vestibular symptoms are related to significant morbidity and decreased quality of life. Methods: Eighty‐nine patients undergoing unilateral VS resection via a retrosigmoid approach during 2008‐2010 were prospectively analyzed. Definitive assessment of vestibular compensation was performed 24 months postoperatively. Persistent vertigo or spontaneous nystagmus and deviation of subjective visual vertical were classified as non‐compensated vestibular pathology. We performed multivariate statistic analysis (Anova) of patient (age, gender), tumor (size – Koos and international classification), preoperative vestibular pathology (ipsilateral/contralateral peripheral, central), and intraoperative (conventional or minimally‐invasive approach, tumor adherence, consistency, bleeding, cystic, origo, cerebellar injury) factors. To assess impact of vestibular symptoms on quality of life, we employed Dizziness Handicap Inventory (DHI) and SF36 questionnaires. Results: Twelve of 89 patients undergoing VS surgery suffered from disordered vestibular compensation. Among the factors analyzed, the advanced age seems to be a crucial negative prospective factor of vestibular compensation ( P =0.006) (55 ± 10 years in noncompensated vs. 44 ± 13 years in compensated patients). Disbalance was more prevalent in the group of uncompensated patients ( P = 4 x 10‐7). Surprisingly, poor compensation did not correlate with worse DHI and SF36 scoring. Conclusions: Identification of factors that may contribute to a poor vestibular compensation is crucial for both VS management planning and proper postoperative vestibular rehabilitation. Employment of biofeedback and vestibular prehabituation represent promising methods to improve and speed up postoperative vestibular compensation.